1978
DOI: 10.1126/science.644329
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Defensive Medicine

Abstract: Defensive medicine--the use of diagnostic and end-treatment measures explicitly for the purposes of averting malpractice suits--is frequently cited as one of the least desirable effects of the current rise in medical litigation. Many physicians and policy-makers claim that defensive medicine is responsible not only for the increasing costs of health care but the exposing of patients to significant risks of harm from unnecessary procedures. Very little solid information is available about defensive medicine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
10

Year Published

1991
1991
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 6 publications
0
38
0
10
Order By: Relevance
“…Some physician surveys have suggested that the practice of defensive medicine is not extensive and is probably not a major contributory cause of escalating health care costs. [4][5][6] In a survey of 162 cardiologists, only 4.4% cited malpractice concerns as the primary reason for choosing to admit a hypothetical patient with atypical chest pain. 7 One possible explanation for this finding is the tendency of physicians to underestimate the influence of malpractice concerns on their use of diagnostic tests; in effect, they fail to acknowledge the degree to which medical standards have been influenced by fear of liability.…”
Section: Editor's Capsule Summarymentioning
confidence: 99%
“…Some physician surveys have suggested that the practice of defensive medicine is not extensive and is probably not a major contributory cause of escalating health care costs. [4][5][6] In a survey of 162 cardiologists, only 4.4% cited malpractice concerns as the primary reason for choosing to admit a hypothetical patient with atypical chest pain. 7 One possible explanation for this finding is the tendency of physicians to underestimate the influence of malpractice concerns on their use of diagnostic tests; in effect, they fail to acknowledge the degree to which medical standards have been influenced by fear of liability.…”
Section: Editor's Capsule Summarymentioning
confidence: 99%
“…The ballooning cost of malpractice claims and insurance has ignited considerable healthcare policy debate and has generated the phenomenon known as defensive medicine (DM), defined as medical practices in which healthcare providers' primary intent is to avoid criticism and lawsuits, rather than providing for patients' medical needs 1,2. Although DM practice is difficult to precisely quantify, investigators have determined that approximately 5–10% of diagnostic tests and therapeutic interventions are performed because of litigation concerns,3,4 and experts have estimated the cost of DM in the United States (U.S.) at $9 to $18 billion annually, consuming approximately 1–2% of U.S. healthcare dollars.…”
Section: Introductionmentioning
confidence: 99%
“…Tancredi and Barondess noted that despite the apparent growing importance of defensive medicine there was very little empirical evidence about the extent of defensive medical practices 6. Most of the current concern arises as a result of a series of surveys conducted in the United States over the past 30 years.…”
Section: Introductionmentioning
confidence: 99%